Clinical outcomes and survival surrogacy studies of prostate‐specific antigen declines following enzalutamide in men with metastatic castration‐resistant prostate cancer previously treated with docetaxel. Issue 12 (7th February 2017) - Armstrong, Andrew J.; Saad, Fred; Phung, De; Dmuchowski, Carl; Shore, Neal D.; Fizazi, Karim; Hirmand, Mohammad; Forer, David; Scher, Howard I.; Bono, Johann De
Abstract : BACKGROUND: In the AFFIRM trial, enzalutamide significantly increased overall survival (OS) for men with metastatic castration‐resistant prostate cancer (mCRPC) after chemotherapy versus placebo and significantly decreased prostate‐specific antigen (PSA) levels. The goal of this post hoc analysis was to associate levels of PSA decline from baseline after enzalutamide with clinical outcomes in the postchemotherapy mCRPC setting. METHODS: Men in the AFFIRM trial (n = 1199) were grouped by maximal PSA decline in the first 90 days of treatment. Kaplan‐Meier estimates evaluated the association of defined PSA changes from baseline with OS, progression‐free survival (PFS), radiographic PFS (rPFS), and pain response. Each PSA decline category was assessed for OS surrogacy using Prentice criteria, proportion of treatment effect explained (PTE), and proportion of variation explained. RESULTS: Men treated with enzalutamide had improved OS (hazard ratio, 0.63; P < .001) and higher rates of PSA decline (odds ratio, >19.0; P < .001) versus placebo. PSA declines of any, ≥30%, ≥50%, and ≥90% with enzalutamide were strongly associated with greater OS, PSA PFS, rPFS ( P < .001), and pain response ( P < .026) versus PSA increase/no decline. Any, ≥30%, and ≥50% declines in PSA resulted in the PTE range of 1.07‐1.29, where treatment was no longer significant after adjustment for decline measures ( P > .20). CONCLUSIONS: PSA declines of any, ≥30%, and ≥50% following enzalutamide were associated with greater clinical and pain response and improvements in PFS and OS. Surrogacy of PSA decline for OS was not fully established, possibly due to lack of PSA declines with placebo, and discordant results between PSA and imaging responses over time, and because some declines were not durable due to rapid resistance development. However, a lack of PSA decline by 90 days following enzalutamide treatment was a poor prognosis indicator in this setting. Conclusions from sensitivity analyses of maximal PSA decline from baseline over the entire treatment period are consistent with PSA declines restricted to the first 90 days. Cancer 2017;123:2303–2311. © 2017 American Cancer Society . Abstract : A post hoc analysis of the randomized, double‐blind AFFIRM trial revealed that postenzalutamide prostate‐specific antigen declines of any, ≥30%, and ≥50% are associated with greater clinical and pain response. The decline criteria explain a large proportion of treatment effect on survival improvements but do not fulfill the criteria for surrogacy.